Neutron yield saturation in plasma focus: A fundamental cause - Lee, S. (AIP Publishing, 2009)
Plasma focus research in the direction of fusion energy faces the limitation of observed neutron saturation; the neutron yield Yn falls away from Yn E0 2 , the scaling deteriorating as storage energy E0 increases toward 1 MJ. Numerical experiments confirm that Yn E0 2 applies at low energies and drops to Yn E0 0.8 toward 25 MJ; deteriorating already at several hundred kilojoules. We point out that the cause is the dynamic resistance of the axial phase that is constant for all plasma foci. This dynamic resistance dominates the circuit as capacitor bank surge impedance becomes insignificant at large E0, causing current, hence neutron “saturation.”